National technical guideline on Mechanized wet direct-seeding for increased productivity, quality, and reduced carbon footprint in rice production in the Mekong River Delta - Department of Crop Production (2023)
The technical guideline of mechanized wet direct-seeding provides information on mechanized wet direct-seeding-related techniques from seed preparation to crop establishment, including (1) Land preparation, (2) Seed preparation, (3) Techniques for operating the seeder (4) Machinery safety, (5) Machine maintenance, (6) Machine troubleshooting in the field and (7) Seeder path planning. Regarding the techniques to operate the seeder, the guideline gives examples for the following seeders: (1) Dynamic air-assisted row seeder (6-row and 16-row type), (2) Hill seeder and (3) Seed cum fertilizer driller.In addition, the guideline also provides a case study of cost-benefit analysis of two investment schemes for mechanized direct seeding service provision, comparing the economic efficiency of mechanized direct seeding with broadcast direct seeding.This technical guideline aims to be a handbook for farmers, extension officers, farmer cooperatives, and individuals working in the field of rice production in the Mekong Delta (MRD); in particular, in the areas for high-quality and low emission rice production.